Omental torsion, an overlooked differential diagnosis of acute abdomen in children. A case series - Ali Z. Elsayed; Anaam R. Alhadeethi; Saifullah Khan; Mohamed E. Hassan; Khalid Al ali (Elsevier, 2021)
Acute surgical abdomen is still forming a diagnostic dilemma in children. Omental torsion was an overlooked differential diagnosis in the era of open appendectomy, but nowadays with the propagation of laparoscopic surgery in pediatric age group there are more reports published describing the omental torsion.Clinical picture of Primary omental torsion is mimicking the diagnosis of acute appendicitis and for most of the cases the diagnosis will be only discovered intraoperatively. Primary omental torsion is more common on the right side of the greater omentum. Free peritoneal serosanguinous fluid is a common intraoperative finding.Due to increasing number of reported cases, omental torsion should always be ruled out in cases of negative laparoscopic exploration for acute abdomen in children. Here we are reporting three cases of omental torsion presented with right lower abdominal pain and primary omental torsion was found during laparoscopic exploration. Laparoscopic excision of the infarcted omentum was done. The clinical course, findings and treatment are highlighted. .